Laser hair removal - Goldberg, David J. (Series in cosmetic and laser theraphy, 2008)
The author of the best-selling text on Laser Hair Removal now returns to the subject. The topic has moved on immensely in the period between editions: of course, there have been technological innovations with lasers themselves - and this text notes the implications of these - but the most important developments have been in the nuanced approach now adopted in practice by cosmetic surgeons. The avoidance of complications, problematic skin, and practical pearls have all assumed a much higher importance, and accordingly these topics now have increased material devoted specifically to them in this text. No practitioner of laser hair removal can afford to be without this improved clinical resource.